Digital Literacy of the State Civil Apparatus in the Administrative Services Unit (ULA) of the Ministry of Home Affairs - Gumanti, Zahwa Nabila; Uluputty, Irfan (Indonesian Journal of Librarianship, 2023)
Background: Digital literacy is crucial for the State Civil Apparatus (ASN) in providing excellent services. Meanwhile, Administrative Services Unit (ULA) has obtained several awards in recognition of outstanding performance, serving as a significant foundation for the current finding. Purpose: This research aimed to describe the digital literacy competency of ASN in ULA to provide excellent services to the public and local governments. Method: A qualitative method with a descriptive approach was selected with the concept of digital literacy competency of ASN to analyze data. In addition, the validity of the findings was tested through data triangulation. Results: The digital literacy results among ASN showed that a fairly good insight with knowledge imbalances, good digital skills, and deficiencies in understanding the risks and the ability to control the dangers of digital technology use. Conclusion: Digital literacy among ASN in ULA shows a commendable level of proficiency and offers opportunities for improvement in certain domains. Keywords: State Civil Apparatus (ASN); Digital Literacy; Administrative Services Unit (ULA)